14-6b+7-2b=1+5b

Simple and best practice solution for 14-6b+7-2b=1+5b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14-6b+7-2b=1+5b equation:


Simplifying
14 + -6b + 7 + -2b = 1 + 5b

Reorder the terms:
14 + 7 + -6b + -2b = 1 + 5b

Combine like terms: 14 + 7 = 21
21 + -6b + -2b = 1 + 5b

Combine like terms: -6b + -2b = -8b
21 + -8b = 1 + 5b

Solving
21 + -8b = 1 + 5b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-5b' to each side of the equation.
21 + -8b + -5b = 1 + 5b + -5b

Combine like terms: -8b + -5b = -13b
21 + -13b = 1 + 5b + -5b

Combine like terms: 5b + -5b = 0
21 + -13b = 1 + 0
21 + -13b = 1

Add '-21' to each side of the equation.
21 + -21 + -13b = 1 + -21

Combine like terms: 21 + -21 = 0
0 + -13b = 1 + -21
-13b = 1 + -21

Combine like terms: 1 + -21 = -20
-13b = -20

Divide each side by '-13'.
b = 1.538461538

Simplifying
b = 1.538461538

See similar equations:

| 5-(2x-1)=x | | 3I+4=4I-3 | | 4(x+3)-1=7 | | -4(w+5)+9=-31 | | 5(m-5)+5=40 | | n+9=3n+5*5 | | -12x+8y=36 | | 35.84=27.02+294.9*x-373.7x | | -1(2n+3)=2(-4-7) | | 20-2(2w+1)=5w-2(5+w) | | 0*3+4=0*2+3 | | n+9=3n+5*4 | | f/7-8=72 | | 8(t+2)-3(t-4)=6(t-7) | | 6-9x=26-23x | | 2x-175=755 | | 26.6x+76.6x+200x=5513 | | 2x+11=-37-10 | | 60=12x | | 5x+4=4555 | | 8x-8y=-16 | | 2x+5x/9=-30 | | f+13=27 | | 7=q-83 | | 6n-4(n-3)=n+3 | | 3x+7=(5x-4)*2 | | 9+(2/3)x=81 | | -7c(3/4)=65 | | 6-4y=y | | 2a-3=3-4a | | 3a-6=10-a | | (2x-2)2=(3x-2)(x-3) |

Equations solver categories